Growth of giant silver dendrites on layer-by-layer assembled films. (20th April 2015) - Song, Jia; Hou, Junxia; Tian, Lili; Guan, Ying; Zhang, Yongjun; Zhu, X.X.
Abstract: Ag dendrites were previously synthesized, with limited success, via the chemical reduction of Ag + ions with a soluble reducing agent in homogeneous solutions. Here Ag + ions were first loaded in hydrogen-bonded layer-by-layer (LBL) films fabricated from poly(vinyl pyrrolidone) (PVPON) and poly(acrylic acid) (PAA), then reduced chemically using p-hydroquinone (HQ) as a reducing agent to afford Ag dendritic structures. The dendrites were characterized by SEM, TEM, XRD and optical microscope. Compared with the Ag dendrites synthesized in homogenous solutions, the dendrites obtained here are much larger. The fully developed ones can reach a size over 600 μm, ca. 2 orders of magnitude larger than those synthesized in homogenous solutions (∼1–5 μm). In addition, the dendrites obtained here are 2 dimensional which grow along the surface of the LBL film, instead of 3 dimensional as those obtained in homogenous solutions. A possible 3-step growth mechanism, which involves the rapid reduction of the Ag + ions in the film, formation of Ag seed particles on the film surface, and fractal dendritic structure formation as described by the diffusion-limited aggregation (DLA) model, was proposed. Graphical abstract: Highlights: Silver dendrites were synthesized by first loading Ag + ions in LBL films and then reducing them using p-hydroquinine. They are two orders of magnitude larger than those synthesized in homogenous solutions. They are 2D structures grown on the film surface.